CLIMATE VULNERABILITY AND LOCAL ADAPTATION STRATEGY: UNDERSTANDING CLIMATE CHANGE NORM ADAPTATION AND DYNAMICS COMMUNITY RESILIENCE IN BATULAPISI DALAM, GOWA REGENCY, SOUTH SULAWESI - Muh. Asy’Ari; Raditya Erlangga (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Climate change presents ecological and social challenges for rural areas, including Batulapisi Dalam, Tinggimoncong District, Gowa Regency, South Sulawesi. The region faces specific vulnerabilities that demand strategic responses to ensure the sustainability of residents’ livelihoods. This research seeks to understand the dynamics of community resilience models through adaptive transformation approaches and the localization of climate norms. A qualitative case study was conducted at the research site using data collection techniques that include in-depth interviews, participatory observation, focus group discussions, and policy document analysis. Our study shows that, despite the intensification of climate impacts displacing planting and harvesting cycles, adaptation to climate-change norms at community levels remains limited. The agrarian pressures brought about by land conflicts and the conversion of agricultural areas into ecotourism sites have further exacerbated these challenges. As a response, farmers have employed agronomic adaptation strategies, especially crop rotation applied to the changing state of groundwater availability. This study proposes a hybrid model for adaptation strategy, integrating socio-ecological capital through livelihood diversification at the rural community level. We argue that linking local policy to national and international frameworks such as the Paris Agreement and the Village SDGs is important and must be pursued together with strengthening norm entrepreneurs who can promote greater local sustainable climate adaptation capacity.